2020
DOI: 10.1103/physrevd.102.076009
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the Ω(2012) state in the Ωc0

Abstract: We report on a theoretical study of the newly observed Ωð2012Þ resonance in the nonleptonic weak decays of Ω 0 c → π þK Ξ Ã ð1530ÞðηΩÞ → π þ ðKΞÞ − and π þ ðKΞπÞ − via final-state interactions of thē KΞ Ã ð1530Þ and ηΩ pairs. The weak interaction part is assumed to be dominated by the charm quark decay process: cðssÞ → ðs þ u þdÞðssÞ, while the hadronization part takes place between the sss cluster from the weak decay and a quark-antiquark pair with the quantum numbers J PC ¼ 0 þþ of the vacuum, producing a pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…MeV [1]. In 2021, evidence of was observed in the weak decay process at Belle [2], following the proposal suggested in Ref. [3].…”
supporting
confidence: 52%
“…MeV [1]. In 2021, evidence of was observed in the weak decay process at Belle [2], following the proposal suggested in Ref. [3].…”
supporting
confidence: 52%
“…It is a challenging issue to fully understand their internal structures. Various theoretical methods and models have been applied in this field, including various quark models [19][20][21][22][23][24][25][26][27][28][29][30], the chiral perturbation theory [31,32], the chiral unitary approach [33], various molecular interpretations [34][35][36][37][38][39], the Regge trajectory [40], the 3 P 0 model [41,42], the relativistic flux tube model [43], QCD sum rules [44][45][46][47][48], and the lattice QCD [49][50][51], etc. We refer to the reviews [9,10,[52][53][54][55] for detailed discussions.…”
Section: Introductionmentioning
confidence: 99%
“…Suggestions on how to observe the Ω(2012) state by looking at Ω c weak decay process have been made in Ref. [52]. It was found that the observed small energy splitting of the Ω 0 c resonances [13], the masses and decay behaviours of the observed Ω(2012) [41][42][43][44] can be well described by taking either the hadronic molecule picture or the compact pentaquark configuration, while it's of course that one cannot rule out the three-quark components in the baryon resonances.…”
Section: Introductionmentioning
confidence: 99%